2015
DOI: 10.1021/acs.inorgchem.5b01924
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Lanthanoid Metal–Organic Framework for Ratiometric Cryogenic Temperature Sensing

Abstract: A ratiometric thermometer based on a mixed-metal Ln(III) metal-organic framework is reported that has good sensitivity in a wide temperature range from 4 to 290 K and a quantum yield of 22% at room temperature. The sensing mechanism in the europium-doped compound Tb0.95Eu0.05HL (H4L = 5-hydroxy-1,2,4-benzenetricarboxylic acid) is based not only on phonon-assisted energy transfer from Tb(III) to Eu(III) centers, but also on phonon-assisted energy migration between neighboring Tb(III) ions. It shows good perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
132
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 176 publications
(134 citation statements)
references
References 52 publications
2
132
0
Order By: Relevance
“…The energy transfer process from Tb III to Eu III in a lanthanide coordination polymer has also been used for a ratiometric luminescent thermosensor . Thermosensitive paints that contain luminescent lanthanide complexes have also been widely investigated …”
Section: Introductionmentioning
confidence: 99%
“…The energy transfer process from Tb III to Eu III in a lanthanide coordination polymer has also been used for a ratiometric luminescent thermosensor . Thermosensitive paints that contain luminescent lanthanide complexes have also been widely investigated …”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported a ratiometric thermometer based on the europium‐doped terbium compound of the ligand 5‐hydroxy‐1,2,4‐benzenetricarboxylic acid, which appeared to be highly sensitive in the cryogenic temperature range of 0–50 K . We further extended our investigations on the temperature‐dependent properties of such lanthanoid coordination polymers; herein we report a ratiometric thermometer based on an La III /Tb III coordination polymer.…”
Section: Introductionmentioning
confidence: 73%
“…Earlier we reported the compounds TbH L and EuH L , which were synthesized using the same ligand H 4 L under the same hydrothermal conditions . The new compound LaH L crystallizes in a different structure, which is most likely due to the different ionic radii of La III , Tb III , and Eu III , .…”
Section: Resultsmentioning
confidence: 95%
“…Suitable MOF designs [54] ensure that the exciton energy can be transferred from several tens to several hundred nanometers. [55] Intriguingly, the structure of MOFs also affects the exciton migration path, as it was discovered that mixed Ru/Os structures constituted 1D or 3D hopping networks. [46] It has been shown that energy transfer by excitons can be described by a Dexter triplet-to-triplet (exchange) mechanism with multistep incoherent exciton hopping, or a Förster mechanism involving one-step jumping over longer distances.…”
Section: Excitonsmentioning
confidence: 99%